GAMBARAN SEXUAL COMPLIANCE PADA REMAJA PEREMPUAN YANG MELAKUKAN PERILAKU SEKSUAL PRANIKAH - Uun Yosie Tigeryani (EXPERIENTIA : Jurnal Psikologi Indonesia, 2020)
Study about sexual compliance is still rarely done in Indonesia. Study about sexual compliance is also often done with quantitative research methods, so that the results of the study are data percentages that describe the surface of sexual compliance. This study aims to explore sexual compliance in-depth in women who engaged in premarital sexual behavior. This study is a qualitative study with a phenomenological research method. The analysis technique of this study is an inductive thematic analysis. The subjects of this study are two teenage girls who engage in unwanted sexual activity. The results of this study are in the form of themes, which are about premarital sexual behavior, sexual compliance, meaning towards sexual compliance experience and about current condition of the subjects.